[P180] Records: Guidelines for publication of monte carlo studies. (August 2018) - Sechopoulos, Ioannis; Rogers, D.W.O.; Bazalova-Carter, Magdalena; Bolch, Wesley E.; Heath, Emily; McNitt-Gray, Michael F.; Sempau, Josep; Williamson, Jeffrey F.
Abstract : Purpose: To improve the description of medical physics studies involving Monte Carlo simulations included in scientific literature by developing a set of recommendations on the information that should be included in this type of manuscript. Methods: An international group of medical physicists with backgrounds in imaging and therapy and with extensive experience in Monte Carlo studies, including the Editor-in-Chief of a medical physics journal, was formed. The group first aimed to identify, by expert opinion, what information is crucial to allow a reader to determine the validity and scope of a Monte Carlo-based study. Then, the level of detail required, and the potential applicability of these items to all or a subset of Monte Carlo studies was discussed. A checklist with the items that were deemed necessary and feasible to describe in a journal manuscript was developed, with the items separated by the sections they belong to in the manuscript. A template for an optional suggested table was also developed in which some of the methods used for the simulation could be described in summary form. Once finalized, the checklist was disseminated among a larger international group of medical physicists experts in Monte Carlo simulations, seeking their and their lab members' feedback on the document. Results: The recommendation checklist includes 20 specific items, affecting the Title, Methods, Results, and Discussion of a manuscript. Some items are very simple (e.g., identifying in the Title that the study is a Monte Carlo study) while others are more extensive (e.g., describing the simulation geometry), with explanation on the level of detail suggested. The feedback on the draft guidelines received from all scientists consulted was very positive, regarding the need for such guidance, the items included in the document, and in its perceived ease-of-use. Conclusions: It is envisioned that the use of these guidelines will improve the description of Monte Carlo studies published in medical physics peer-reviewed literature. In addition to potentially providing a reference for authors and journal reviewers, the guidelines could be especially useful for scientists entering the field and writing their first manuscript. The RECORDS guidelines can be found at https://doi.org/10.1002/mp.12702 .